RASA4 inhibits the HIFα signaling pathway to suppress proliferation of cervical cancer cells. Issue 2 (20th December 2021) - Chen, Junying; Huang, Jinbing; Huang, Qiaoqiao; Li, Ji; Chen, Erling; Xu, Wensheng
ABSTRACT: RAS p21 protein activator 4 (RASA4) has been recognized as a Ca 2+ -promoted Ras–MAPK pathway suppressor that inhibits tumor growth. However, the role of RASA4 in cervical squamous cell carcinoma (CESC) remains unclear. The mRNA levels of RASA4 were analyzed using the GEO and GEPIA databases. Kaplan–Meier analysis and ROC analyses were conducted to determine the prognostic and diagnostic values for patients from the TCGA-CSCE cohort. The CCK8 and colony assays were performed to assess the impact of RASA4 ectopic expression and gene inactivation on tumor cell proliferation. In vivo experiments were performed. Luciferase reporter assays and LW6 (a HIFα inhibitor) were employed to verify the regulatory relationship between RASA4 and the HIFa signaling pathway. The GEPIA and GEO database analysis demonstrated poorly expressed RASA4 in the CESC tissues relative to that in the noncancerous tissues. Based on the TCGA database, poorly expressed RASA4 signified high prognostic and diagnostic values. Ectopically expressed RASA4 weakened the proliferative potential of HeLa cells, whereas RASA4 genetic inactivation produced the opposite impact in the HeLa and C-33A cells. The promoting effect of RASA4 deficiency on tumourigenesis was also recorded in vivo . Subsequently, RASA4 negatively regulated the HIFα-driven luciferase activities and weakened the expression of survivin. Meanwhile, LW6 treatment abrogated the increased proliferation of HeLa cells, as well as the increased expression of survivin by RASA4 depletion. Our findings indicated that RASA4 can inhibit the proliferation of cervical cancer cells by inactivating the HIFα signaling pathway, suggesting novel prospects for targeted therapy against CESC.